ANALYZING THE IMPACT OF BIG DATA CREDIT TECHNOLOGY ON MICRO AND SMALL ENTERPRISES (MSE s ) CREDIT ACCESS: AN EVOLUTIONARY GAME PERSPECTIVE IN INDONESIA - Zaenal Aripin; Diah Fatma Sjoraida; Nyoman Dwika Ayu Amrita (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
The use of big data credit technology has become a significant trend in the financial industry in Indonesia, with the potential to impact credit access for micro and small enterprises (MSEs). In this context, evolutionary games become a relevant analytical framework for understanding the dynamics of interactions between financial institutions, MSEs and governments in the use of this technology. This study aims to analyze the impact of big data credit technology on MSE credit access in Indonesia, as well as the government's role in regulating the use of this technology and increasing digital inclusivity for MSEs. By utilizing a literature study approach, related articles and reports were analyzed to gain insight into key issues in the use of big data credit technology and evolutionary gaming in Indonesia. From the analysis carried out, it was found that the use of big data credit technology has a significant impact on MSE credit access. While this technology brings benefits in the form of expanded access and increased process efficiency, challenges such as data protection and inequality of access also need to be addressed. In the dynamics of this evolutionary game, governments play an important role in regulating the use of these technologies, ensuring adequate data protection and increasing digital inclusivity for MSEs. Strict but balanced regulation is needed to ensure that the benefits of the use of big data credit technology are enjoyed equally by all parties, while minimizing the risks associated with the use of consumer data. Apart from that, the government also needs to continue their efforts to facilitate digital inclusivity for MSEs through programs such as providing affordable internet access and digital training.